Practical diets with essential oils of plants activate the complement system and alter the intestinal morphology of Nile tilapia - Valladão, Gustavo M. R. [UNESP]; Gallani, Sílvia U. [UNESP]; Pala, Gabriela [UNESP]; Jesus, Raphael B. [UNESP]; Kotzent, Suzana [UNESP]; Costa, Jaqueline C. [UNESP]; Silva, Thiago F. A. [UNESP]; Pilarski, Fabiana [UNESP] (Hindawi, 2017)
The effect of the essential oils (EOs) of peppermint, Mentha piperita L., and tea tree, Melaleuca alternifolia (Maiden & Betche) Cheel, on the haematological, biochemical, and immunological parameters and intestinal morphology of Nile tilapia, Oreochromis niloticus L., was evaluated. Fish (58.09 ± 5.87 g) were fed 100 mg/kg and 250 mg/kg of each EO and sampled on days 7, 14, 30 and 60 after starting supplementation. The haematological and biochemical parameters were not altered by the supplementation of EOs compared to the control (p >.05). With regard to the immunological parameters, the activation of the complement system of fish fed 250 mg/kg peppermint and 100 mg/kg and 250 mg/kg tea tree EOs were significantly higher compared to the control after 60 days of feeding (p <.05). The complement system plays an essential role in innate immunity and contributes significantly to the acquired immune response; thus, its activation through supplementation with EOs is promising for the formulation of nutritional additives in aquaculture. Regarding intestinal morphology, fish fed 250 mg/kg tea tree EO presented higher villus size compared to all other groups (p <.05), which represents a healthier gut. These fish present a larger intestinal surface, which can result in better absorption and utilization of the nutrients. Based on the responses found in this study, both EOs were considered promising for the formulation of feed additives for Nile tilapia.
Keywords: aquaculture; immunostimulant; Melaleuca alternifolia; Mentha piperita; phytotherapy; plant extract